Brain functional network integrity sustains cognitive function despite atrophy in presymptomatic genetic frontotemporal dementia - Tsvetanov, Kamen A. (Alzheimers Dement, 2021)
INTRODUCTION: The presymptomatic phase of neurodegenerative disease can last many years, with sustained cognitive function despite progressive atrophy. We investigate this phenomenon in familial Frontotemporal dementia (FTD). METHODS: We studied 121 presymptomatic FTD mutation carriers and 134 family members without mutations, using multivariate data-driven approach to link cognitive performance with both structural and functional magnetic resonance imaging. Atrophy and brain network connectivity were compared between groups, in relation to the time from expected symptom onset. RESULTS: There were group differences in brain structure and function, in the absence of differences in cognitive performance. Specifically, we identified behaviourally-relevant structural and functional network differences. Structure-function relationships were similar in both groups, but coupling between functional connectivity and cognition was stronger for carriers than for non-carriers, and increased with proximity to the expected onset of disease. DISCUSSION: Our findings suggest that maintenance of functional network connectivity enables carriers to maintain cognitive performance.